Western and Eastern Perspectives of Feminism - Mazhar Alvi, Faiza; Azwar Abbas, Syed; zafar, Jawaria (sourcecoder, 2022)
In this article the key perspectives of feminism with respect to east and west has been discussed. Every movement in literature or with socio-political aspects has some reasons or specific phenomena’s behind it. East and west with respect to feminism deals with the social, political, professional and personal rights of women, the rights which was abandoned during the dark ages of Europe and the movement of feminism has its origin in the west (France) with a lot of influence on international level especially in east. Feminism has grown with the help of literature all around the world. It discusses women’s rights to establish civilized societies. In western and eastern perspective, the basic demand with every aspect of life is, to deal with women as a human first.